Reconceptualizing green sukuk through Maqashid al-Shariah for advancing sustainable development goals - Izzati, Amrina Nur; Tumuyu, Sri Setiawati; Wardhana, Yuki Mahardhito Adhitya (Journal of Islamic Economics Lariba, 2025)
IntroductionThe global pursuit of sustainable development has intensified the need for innovative financing instruments capable of addressing environmental and social challenges while remaining ethically grounded. In Muslim-majority countries, green sukuk has emerged as a promising Islamic finance instrument designed to fund environmentally friendly projects in line with Shariah principles. Despite its growing relevance, scholarly discussion on how green sukuk operationalizes maqashid al-shariah within the framework of the Sustainable Development Goals remains limited, particularly from an integrated conceptual and stakeholder-based perspective.ObjectivesThis study aims to develop and analyze a green sukuk concept based on maqashid al-shariah in achieving sustainable development. Specifically, it seeks to examine the alignment between green sukuk, maqashid al-shariah, and the Sustainable Development Goals; identify priority dimensions in green sukuk development; and assess key implications for investors, governance, and public policy in the Indonesian context.MethodThe study adopts a qualitative-descriptive approach combined with an Analytic Hierarchy Process. Data were collected from secondary sources, including official green sukuk allocation and impact reports, and primary data obtained through interviews and structured questionnaires involving key stakeholders. Content analysis was used to map green sukuk–financed projects to maqashid al-shariah and Sustainable Development Goals, while the Analytic Hierarchy Process was employed to determine priority dimensions in green sukuk development.ResultsThe findings reveal a strong alignment between green sukuk, maqashid al-shariah, and the Sustainable Development Goals, particularly in environmental protection, social welfare, and economic resilience. Environmental and social dimensions emerge as the highest priorities, surpassing economic and governance considerations. However, the study identifies an imbalance in maqashid realization, with intellectual development receiving limited attention. Investor participation is largely driven by functional value considerations, while governance quality and transparency play a critical enabling role.ImplicationsThe results highlight the need for more holistic maqashid-based frameworks that integrate intellectual development, strengthen governance, and enhance sustainability reporting to improve the effectiveness and credibility of green sukuk.Originality/NoveltyThis study offers an integrated maqashid al-shariah–based conceptualization of green sukuk linked explicitly to the Sustainable Development Goals, combining content analysis with stakeholder prioritization to advance the discourse on Islamic sustainable finance.